1989
DOI: 10.1143/jjap.28.l784
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity Change in Structural Modulation in Bi2Sr2Ca1-yREyCu2O8+δ (RE=Y, Nd) System

Abstract: Changes in structural modulation for the Bi2Sr2Ca1-y RE y Cu2O8+δ system (RE=Y, Nd), accompanied with the transition from the superconductor to the antiferromagnetic insulator, were examined. In the Bi2Sr2Ca1-y Y y Cu2O8+δ system, the modulation periodicity continuously decreased, from about 5.0 times to 4.0 times the length of the subcell along the b axis, with increasing Y content substituted. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Regarding the origin of the SC structure, the intercalation of extra oxygen in BiO layer has been studied, 1,2,11,13 and the extra oxygen model seems to be widely accepted in several proposed models. Among those studies, the interca-lation was carried out by aliovalent substitution such as the partial substitution of La 3+ for Sr 2+ , Pb 2+ for Bi 3+ , 1,2 or 3d metals for Cu, 14 etc.…”
Section: Structural Modulation On Multilayered Bismuth Cuprate Observmentioning
confidence: 99%
“…Regarding the origin of the SC structure, the intercalation of extra oxygen in BiO layer has been studied, 1,2,11,13 and the extra oxygen model seems to be widely accepted in several proposed models. Among those studies, the interca-lation was carried out by aliovalent substitution such as the partial substitution of La 3+ for Sr 2+ , Pb 2+ for Bi 3+ , 1,2 or 3d metals for Cu, 14 etc.…”
Section: Structural Modulation On Multilayered Bismuth Cuprate Observmentioning
confidence: 99%
“…Reciprocal space of such structure shows satellite peaks around the main reflection generated by unit cell structure. While symmetric fourfold satellites in intensity and distribution have been observed on single crystal [1][2][3][4][5][6][7][8][9], asymmetric satellite peaks were observed by X-ray reciprocal space mapping (XRSM) on epitaxial thin film [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on single crystal using high-resolution electron microscopy, electron diffraction, X-ray diffraction (XRD), and neutron diffraction on single crystal samples [1][2][3][4][5][6][7][8][9][10][11]. However, detailed studies have not been reported on epitaxial film.…”
Section: Introductionmentioning
confidence: 99%